Analysis of Factors Causing Employee Performance in Health Service Sector - Melan Damayanti; Andreas Wahyu Gunawan; Mutiara Sibarani Panggabean (International Journal Labs, 2023)
People are important resources for the achievement of the vision and mission of the company's organization as a whole. HR development is the process of making employees better and better able to help a company achieve its goals. This study aims to test and analyze